Abiotic an biotic degradation of reactive blends of polylactic acid - thermoplastic cassava starch reinforced with graphene nanoplatelets - Bher, Anibal Ricardo (2019)
Biofilms of PLA, thermoplastic cassava starch (TPCS), and graphene nanoplatelets (GNP) were evaluated for abiotic and biotic degradation under simulated composting conditions at ~58 °C, ~50% of relative humidity (RH) and 120 days in compost. The evolved CO2, mineralization, and molecular number (Mn) were measured. A reduction of Mn was observed for PLA, indicating abiotic degradation. A priming effect was observed for the physical blend (PLA-TPCS), associated with the overproduction of CO2. A significant biodegradation rate was observed for TPCS phase. GNP at 1% produced a reduction in the lag phase of PLA and PLA-g-TPCS (reactive blend).